ISOLASI, IDENTIFIKASI DAN PEMURNIAN SENYAWA 1,8 SINEOL MINYAK KAYU PUTIH (Malaleuca leucadendron) - Rizqi Helfiansah; Hardjono Sastrohamidjojo; Riyanto - (ASEAN Journal of Systems Engineering, 2013)
Cajuput  oil  is one of the  essential oils that  widely used  as materials for  medical  or pharmaceutical products, this makes the cajuput oil become the most wanted products in essential oils industries. Cajuput oil demand is currently increasing with the growing variety of utilization of cajuput oil. Cajuput oil productions in Indonesia run into fluctuations and tend to decrease. There are several factors that affect production and quality of cajuput oil, and one of them is distillation technique. Moreover fractionation or isolation of the 1,8-cineol compound also have not been done by the cajuput oil entrepreneurs, whereas this is important in order to use 1.8 cineol compound further.Distillation of cajuput leaves is done by three distillation methods, namely water distillation, water steam distillation and steam distillation. Calculating the yield after cajuput oil obtained and then testing the physical and chemical properties of cajuput oil in accordance with the Indonesia National Standard (SNI 06-3954-2006). And then doing fractionation of cajuput oil to obtain at least 85% 1,8 Cineol compound.            The results showed that water steam distillation method produces the highest yield, the yield is  2.5%, followed by water distillation method, the yield is 1.8% and then steam distillation method, the yield is 1.5%. Physical and chemical properties that exist on cajuput oil that produced by water and steam distillation method and steam distillation method are appropriate with the Indonesia National Standard. After doing fractination processes for two time, the fractination process produced 1.8 cineol compound 79.90% in first fraction, 87.90% at second fraction and then 89.78% at third fraction.